Relationship between Mothers' Attitudes with Diarrhea Prevention in Toddlers - Ridawati, Indah Dewi; Nugroho, Bintoro (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The prevalence of diarrhea diseases is increasing, the total cases of diarrhea diseases listed in the Work Area Air Lais sub-district Community Health centers Padang Jaya in 2014 reached 230 cases. The purpose of this research is to determine the relationship between mothers’ attitudes with prevention of diarrhea disease in toddlers. This research is a quantitative research with cross sectional design. The sample in this study were mothers with children under five by purposive sampling technique. The participants of this research was 95 mothers and statistical analysis using chi square. Results of the analysis found correlation between maternal attitudes with efforts to prevent diarrhea disease in toddlers (ρ value = 0.000). Expected health workers can improve the promotion for better health and increasing efforts to prevent diarrhea diseases that can be carried by mothers as a prevention of diarrhea disease in Toddlers.